Perbedaan Perilaku Hidup Bersih dan Sehat Saat Pandemi Covid-19 Sebelum dan Sesudah Promosi Kesehataan Pada Siswa Kelas XI MAN 20 Jakarta Tahun 2021 - Maghfira Rizka Rahayu, (2021)
Clean and healthy living behavior is the basis for health behavior in various structurs, including school structurs in improving health status. In 2020 there was a covid-19 pandemic that can infect human including school-age teenagers and the prevention that can be done is through PHBS, for that it is necessary to promote health regarding PHBS during the covid-19 pandemic in adolescents. This study aims to determine and analyze the differences in PHBS during Covid-19 before and after health promotion in class 11th MAN 20 Jakarta. This type of research uses a quasi-experimental method with a one group prettest-posttest design conducted in April-June 2021. The population of this study were all students of class XI MAN 20 Jakarta with a total sample of 105 students using purposive sampling technique. The instrument used is a questionnaire in the form of a google form. This study used the Wilcoxon test. The results showed that there were differences in knowledge before and after health promotion, with a value of z = -3.051 with a P Value of .002 (P Value < 0.05), there were differences in attitudes before and after health promotion with a value of z = -3.269 with a P Value of .001 ( P Value < 0.05), there are differences in actions before and after health promotion with a value of z = -3.230 with a P Value of .001 (P Value < 0.05). The conclusion of this study is that there are differences in knowledge, attitudes, and actions between before and after health promotion..